2022
DOI: 10.2478/jtim-2022-0068
|View full text |Cite
|
Sign up to set email alerts
|

Focal liver lesions other than hepatocellular carcinoma in cirrhosis: Diagnostic challenges

Abstract: Liver cirrhosis is associated with regenerative nodules and an increased risk of developing hepatocellular carcinoma (HCC). However, other benign and malignant liver lesions may also occur. Differentiating the other lesions from HCC is important for further therapeutic decisions. This review discusses the characteristics of non-HCC liver lesions in cirrhosis and their consequent appearance on contrast-enhanced ultrasonography (CEUS) with consideration of other imaging. Knowledge of this data would be helpful i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 109 publications
0
9
0
1
Order By: Relevance
“…Penyebab sirosis sangat bervariasi di setiap negara (Mittal et al, 2016). Sirosis hati dikaitkan dengan nodul regeneratif dan peningkatan risiko pengembangan karsinoma hepatoseluler (HCC) (Möller et al, 2022). Karsinoma hepatoseluler adalah bentuk paling umum dari kanker hati.…”
Section: Pendahuluanunclassified
“…Penyebab sirosis sangat bervariasi di setiap negara (Mittal et al, 2016). Sirosis hati dikaitkan dengan nodul regeneratif dan peningkatan risiko pengembangan karsinoma hepatoseluler (HCC) (Möller et al, 2022). Karsinoma hepatoseluler adalah bentuk paling umum dari kanker hati.…”
Section: Pendahuluanunclassified
“…sarcoidosis [20][21][22][23], tuberculosis [24,25], hydatid cysts [26][27][28][29], alveolar echinococcosis [27], schistosomiasis [30,31], ascariasis [32,33], fasciolosis [34], clonorchis and opisthorchis [35], toxocariasis [36], bacillary angiomatosis [37], and amyloidosis with spontaneous hemorrhage [38], as well as rare FLLs in pediatric patients [39,40]. More recently rare bacterial [41], parasitic [42], and autoimmune focal liver lesions [43], bile duct lesions [44], other benign FLL [45,46], and FLL other than HCC in the cirrhotic liver [47,48] have been featured as well [41][42][43]49].…”
Section: Introductionmentioning
confidence: 99%
“…Liver cancer resection, especially in patients with hemihepatectomy or extended hemihepatectomy, often leads to poor prognosis, such as liver insufficiency and even liver failure and death, because the standard residual liver volume (SRLV) cannot be fully compensated after surgery[ 10 ]. Research suggests that preoperative liver fibrosis and cirrhosis are the main causes[ 11 ]. In recent years, an increasing number of studies have shown that the liver stiffness measure (LSM) value is significantly related to the degree of cirrhosis, which can reflect the degree of liver inflammation and fibrosis[ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%